Posterior polymorphous dystrophy: an unusual presentation - Muhammad Syamil MS; Umi Kalthum MN; Jemaima Che Hamzah (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Posterior Polymorphous Dystrophy (PPD) is a rare, innocuous and asymptomatic condition in which corneal endothelial cells display characteristics similar to epithelium. It is often bilateral and frequently asymmetric. We report a case of a 10-year-old girl with a family history of glaucoma who presented with right eye blurring of vision since few years. She had frequent spectacle-prescription changing due to unimproved visual acuity. Cycloplegic refraction revealed high astigmatism and moderate amblyopia over the right eye. Her best corrected vision was 6/9 for the right and left eyes. Slit-lamp examination showed a vesicular-like lesion at the periphery of corneal endothelial layers in both eyes. Endothelial cell density was much reduced on the right eye compared to the left, with more severe astigmatism. Other ocular examinations were unremarkable. Patient was instructed to patch her better left eye periodically. Although patients with Posterior Polymorphous Dystrophy (PPD) present at the age of adulthood, the age at diagnosis is highly variable. It is rare and inherited through an autosomal dominant pattern. PPD may rarely lead to astigmatism, by which was present in the patient due to the features of non-keratoconic and keratoconic cornea on the right and left eye, respectively. Endothelial cell counts were reduced more on the right eye compared to the left, which later may worsen her visual acuity thus indicating corneal transplant in the future. Patient also had a strong family history of glaucoma. Hence, screening of associated disease of corneal endothelial dystrophy in the family may be necessary.